Physicochemical Properties of Nanomaterials: Implication in Associated Toxic Manifestations. (6th August 2014) - Gatoo, Manzoor Ahmad; Naseem, Sufia; Arfat, Mir Yasir; Mahmood Dar, Ayaz; Qasim, Khusro; Zubair, Swaleha
Abstract : Nanotechnology has emerged as one of the leading fields of the science having tremendous application in diverse disciplines. As nanomaterials are increasingly becoming part of everyday consumer products, it is imperative to assess their impact on living organisms and on the environment. Physicochemical characteristics of nanoparticles and engineered nanomaterials including size, shape, chemical composition, physiochemical stability, crystal structure, surface area, surface energy, and surface roughness generally influence the toxic manifestations of these nanomaterials. This compels the research fraternity to evaluate the role of these properties in determining associated toxicity issues. Reckoning with this fact, in this paper, issues pertaining to the physicochemical properties of nanomaterials as it relates to the toxicity of the nanomaterials are discussed.